The role of thyroid dysfunction in the development of benign breast diseases in women of reproductive age (Uzbekistan Open Conference, 2026)
Thyroid dysfunction is considered one of the important endocrine-metabolic factors in the development of benign breast diseases in women of reproductive age. Alterations in thyroid hormone metabolism affect cellular proliferation processes and contribute to the development of fibrocystic and diffuse proliferative changes in breast tissue [S. Chopra, 2023; Tang, 2024]. In particular, subclinical and overt hypothyroidism associated with iodine deficiency has been reported to increase the risk of benign breast diseases, including mastopathy [P. Prudhvini, 2024]. Recent clinical studies have confirmed the presence of pathogenetic and hormonal relationships between thyroid status and proliferative changes in breast tissue [Y. Zheng, 2024; C.M. Kitahara, 2023]. Benign breast disorders were identified in 15 of 27 patients (55.6%), predominantly fibrocystic changes and diffuse mastopathy. The mean TSH level was 5.1 ± 1.3 mIU/L and the mean prolactin level was 402 ± 88 mIU/L; at TSH levels > 4.0 mIU/L, the risk of mastopathy increased more than two-fold (OR = 2.41; 95% CI 1.02–5.71; p = 0.04) and was associated with increased breast tissue density (p = 0.03). After correction of iodine deficiency and normalization of thyroid function, 9 of 15 patients (60.0%) demonstrated a reduction in mastalgia severity, a decrease in cyst size by 3.8 ± 1.1 mm (p = 0.02), and a trend toward regression of structural changes; achievement of euthyroidism increased the probability of clinical improvement (OR = 1.87; 95% CI 0.96–3.65; p = 0.06).